Application of Ecological Teaching Model in College English Speech and Writing Courses: A Pedagogical Study (Journal of Global Humanities and Social Sciences, 2025)
Amid digital transformation, developing ecologically-oriented speech and writing courses addresses not only language skill development but also responds to China’s strategic initiative of enhancing global storytelling. This study investigates ecological pedagogy in college-level English public speaking and writing instruction, targeting students' persistent difficulties in oral and written expression. Drawing on educational ecology principles that frame language learning as dynamic learner-environment interactions, the research establishes three core teaching principles: holistic integration, dynamic adaptation, and diversified engagement. By analyzing the curriculum framework and learner characteristics at the researcher's university, a three-dimensional framework synergizing linguistic, cultural, and technological dimensions was designed. Through three iterative teaching cycles supported by quantitative data and qualitative feedback, the study demonstrates how responsive ecological adjustments optimize instructional effectiveness. These findings provide implementable strategies for analogous programs while advancing sustainable innovation in collegiate English education.